Intermediate accounting : volume 1 - Robles, Nenita S.; Patricia M. Empleo (Mandaluyong City, Philippines : Millenium Books, Inc., 2016)
This book Volume 1, which focuses on accounting for assets integrates all the applicable requirements of the following financial reporting standards.
Chapter 1: The Development of the Accounting Profession -- Chapter 2: Cash and Cash Equivalents -- Chapter 3: Receivables -- Chapter 4: Inventories -- Chapter 5: Property, Plant and Equipment -- Chapter 6: Intangible Assets -- Chapter 7: Investments in Debt and Equity Securities -- Chapter 8: Investment Property, Other Non-current Financial Assets and Non-current Assets Held for Sale -- Chapter 9: Biological Assets.
Includes bibliographical references.
Keywords: INTERMEDIATE ACCOUNTING